Tau Pathology Drives Disease‐Associated Astrocyte Reactivity in Salt‐Induced Neurodegeneration - Tong‐Yu Rui; He‐Zhou Huang; Kai Zheng; Hong‐Wei Fan; Juan Zhang; Zi‐Yuan Guo; Heng‐Ye Man; Nadezhda Brazhe; Alexey Semyanov; You‐Ming Lu; Dan Liu; Ling‐Qiang Zhu (Advanced Science)
Abstract Dietary high salt intake is increasingly recognized as a risk factor for cognitive decline and dementia, including Alzheimer’s disease (AD). Recent studies have identified a population of disease‐associated astrocytes (DAA)‐like astrocytes closely linked to amyloid deposition and tau pathology in an AD mouse model. However, the presence and role of these astrocytes in high‐salt diet (HSD) models remain unexplored. In this study, it is demonstrated that HSD significantly induces enhanced reactivity of DAA‐like astrocytes in the hippocampal CA3 region of mice, with this reactivity being critically dependent on neuronal tau pathology. Neuronal tau pathology activates adenosine A1R signaling, exacerbating tau pathology by inhibiting the Cers1 pathway, which sustains astrocyte reactivity. Additionally, neurons burdened with tau pathology promote astrocyte reactivity via releasing Proteins Associated with Promoting DAA‐like Astrocyte Reactivity (PAPD), with Lcn2 playing a pivotal role. Knockout of Lcn2 or its receptor 24p3R significantly mitigates HSD‐induced DAA reactivity and neuroinflammation. These findings suggest a vicious cycle between tau pathology and A1R signaling, driving DAA‐like astrocyte reactivity. Targeting the Tau‐A1R axis may provide a novel therapeutic strategy for reducing HSD‐induced neuroinflammation and cognitive deficits.